Association Between Vaso-Occlusive Crises and Opioid Prescriptions Among Patients with Sickle Cell Disease: A Retrospective Claims-Based Study - Hyeun Ah Kang; Jamie C. Barner; Kristin M. Richards; Menaka Bhor; Jincy Paulose; Abdullah Kutlar (Journal of Health Economics and Outcomes Research)
**Background/Objectives:** Among sickle cell disease (SCD) patients, vaso-occlusive crises (VOCs) are recurrent and unpredictable attacks of acute pain. These pain crises are often treated with analgesics, including opioids, which have been associated with misuse and overdose. The aim of this study was to examine the association between VOC events and opioid use and assess the association between opioid prescriptions and health care resource utilization among SCD patients. # Methods This was a retrospective cohort study using Texas Medicaid medical and prescription claims between September 2011 and August 2016. The index date was the first SCD diagnosis. Patients (2–63 years) with at least one inpatient or two outpatient SCD diagnoses, who were continuously enrolled during 12 months postindex, were included in the study. The primary outcome was number of opioid prescriptions, while the independent variable was number of VOC events. Covariates included age, gender, nonopioid medication use, nonstudy SCD-related medication (penicillin and folic acid) use, evidence of blood transfusions, number of SCD-related complications, number of SCD-related comorbid conditions, and Charlson Comorbidity Index score. Negative binomial regression analysis was used to address study objectives.